Comparative Analysis of Osteoarthritis Therapeutics: A Justification for Harnessing Retrospective Strategies via an Inverted Pyramid Model Approach - Quinn T. Ehlen; Jacob Jahn; Ryan C. Rizk; Thomas M. Best (Biomedicines)
In this review, we seek to explore two distinct approaches to the clinical management of OA: a prospective approach, addressing primarily one’s genetic predisposition to OA and generating early intervention options, and the retrospective approach, aimed at halting or reversing OA progression post-symptom onset. The clinical management of OA remains challenging, largely due to the limited availability of preventative treatments and failure of existing therapies to modify or reverse the underlying pathophysiology. The prospective approach involves the identification of genetic markers associated with OA and utilizes in vitro and in vivo models to characterize the underlying disease mechanism. Further, this approach focuses on identifying genetic predispositions and unique molecular subtypes of OA to develop individualized treatment plans based on patient genotypes. While the current literature investigating this strategy has been notable, this approach faces substantial challenges, such as extensive time burdens and utilization of extensive genetic testing that may not be economically feasible. Additionally, there is questionable justification for such extensive investigations, given OA’s relatively low mortality rates and burden when contrasted with diseases like specific forms of cancer, which rely heavily on the prospective approach. Alternatively, the retrospective approach primarily focuses on intervention following symptom onset and aims to utilize novel therapeutics to slow or reverse the inflammatory cascade typically seen in disease progression. These treatments, like Hippo pathway inhibitors, have shown initial promise in halting OA progression and alleviating OA symptomology by modulating cellular processes to preserve articular cartilage. In comparison to the prospective approach, the retrospective strategy is likely more cost-effective, more widely applicable, and does not necessitate thorough and invasive genetic screening. However, this approach must still be weighed against the typical natural history of disease progression, which frequently results in total knee arthroplasty and unacceptable outcomes for 15–20% of patients. From a comparative analysis of these two approaches, this review argues that the retrospective strategy, with ideally lower time and economic burden and greater accessibility, offers a more reasonable and effective solution in the context of OA management. Using a similar approach to other management of chronic diseases, we suggest an “Inverted Pyramid” model algorithm, a structured research and development regimen that prioritizes generating widely effective therapies first, with subsequent refinement of treatments based on the development of patient resistance to these therapies. We argue that this strategy may reduce the need for total knee arthroplasty while improving patient outcomes and accessibility.